Mucosal expression and luminal release of epidermal and transforming growth factors in patients with duodenal ulcer before and after eradication of Helicobacter pylori. Issue 4 (April 1997) - Konturek, P C; Ernst, H; Konturek, S J; Bobrzyński, A J; Faller, G; Klingler, C; Hahn, E G
Abstract : BACKGROUND: Epidermal growth factor (EGF) and transforming growth factor-alpha (TGF alpha) are potent gastric acid inhibitors and stimuli of mucosal growth and protection but their involvement in Helicobacter pylori associated duodenal ulcer has been little examined. AIM: To assess gastric acid secretion, plasma gastrin concentrations, mucosal content of EGF and TGF alpha, and mucosal expression of these peptides and their receptor (EGFr) as well as salivary and gastric luminal release of EGF under basal conditions and after pentagastrin stimulation in 10 healthy subjects and in 25 H pylori positive patients with duodenal ulcer before and after two weeks of triple anti-H pylori therapy and four weeks after the termination of this therapy. RESULTS: Pentagastrin stimulation caused a significant increase in salivary and gastric release of EGF both in healthy controls and patients with duodenal ulcers but in the patients, the eradication of H pylori resulted in several fold higher gastric luminal (but not salivary) EGF release than before the anti-H pylori therapy. Mucosal contents of immunoreactive EGF and TGF alpha and mucosal expression of EGF, TGF alpha, and EGFr in H pylori positive patients with duodenal ulcer were significantly higher than those in healthy H pylori negative controls and this increase persisted after eradication of H pylori. Basal plasma gastrin was significantly reduced after two weeks of triple therapy and four weeks after the H pylori eradication all ulcers were completely healed. CONCLUSIONS: (1) H pylori infection in patients with duodenal ulcer was accompanied by enhanced plasma gastrin and increased mucosal content and expression of TGF alpha, EGF, and EGFr; (2) H pylori eradication resulted in ulcer healing, reduction in plasma gastrin, and enhancement of gastric (but not salivary) luminal release of EGF, particularly after pentagastrin stimulation; and (3) enhanced mucosal content and expression of TGF alpha, EGF, and EGFr and increased luminal release of EGF may contribute to ulcer healing after eradication of H pylori.